Yangian in the twistor string - Corn, John; Creutzig, Thomas; Dolan, Louise (Journal of High Energy Physics, 2010)
We study symmetries of the quantized open twistor string. In addition to global PSL(4|4) symmetry, we find non-local conserved currents. The associated non-local charges lead to Ward identities which show that these charges annihilate the string gluon tree amplitudes, and have the same form as symmetries of amplitudes in N = 4 super conformal Yang Mills theory. We describe how states of the open twistor string form a realization of the PSL(4|4) Yangian superalgebra. © SISSA 2010.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Conformal field models in string theory; Gauge-gravity correspondence; Global symmetries